Short‐term reproducibility and variability of the pupillographic sleepiness test. Issue 6 (20th May 2015) - Wilhelm, Barbara; Bittner, Evelyn; Hofmann, Anna; Koerner, Andreas; Peters, Tobias; Lüdtke, Holger; Wilhelm, Helmut; Gurri, Francisco D.; Ortega‐Muñoz, Allan
<x xml:space="preserve">Abstract</x> Objectives The pupillographic sleepiness test (PST) measures the amplitude of the fluctuations of pupil size in the dark, which reflects the level of central nervous system activation and thus alertness. The aim of this study was to assess the short‐term reproducibility and variability of the results obtained with the PST in normal healthy subjects. Methods The PST was measured at 9.00, 11:00, and 13:00 h on three consecutive days in 13 young adults. Subjective sleepiness was assessed with the Stanford Sleepiness Scale (SSS) and with a Visual Analogue Scale (VAS). The intra‐class correlation (ICC), a measure of reproducibility and the intra‐ and inter‐individual variability, was calculated. Results ANOVA analysis of the data revealed no significant differences in the PST measurements for testing day. Time of day and subject did however significantly affect the results with an ICC 73.1%. For the SSS and VAS, the ICC was 38.8% and 45.9%, respectively. The intra‐ and inter‐individual variability in PST results did not differ considerably between time and days. Conclusions We conclude that recordings of the PST have a good reproducibility and low intra‐ and inter‐individual variability compared to subjective scales of sleepiness or the Multiple Sleep Latency Test. The PST is thus a viable method to measure daytime sleepiness objectively. Am. J. Hum. Biol. 27:862–866, 2015. © 2015 Wiley Periodicals, Inc.